Dual memory - Burke, Sue, 1955- (Tor, 2023)
"Antonio Moro lost everything to the Leviathan League. Now he's alone in a city on an Arctic island fighting the ruthless, global pirates with the chance to be the artist he always wanted to be. Unfortunately, he thinks it's a cover story for his real purpose-spying on sympathizers. When things look bleak, he discovers an unusual ally. His new personal assistant program, Par Augustus. It's insolent, extroverted, moody, and a not-quite-legal nascent A. I. Together they create a secret rebellion from unlikely recruits to defend the island from ideological pirates with entitlement and guns, and capitalist pirates with entitlement and money."--